The Effectiveness of the Pertamina Cirebon Hospital CSR Program as A Form of Communication Between the Company and the Surrounding Community - Jaladri, Firda Fadillah; Maulidiyah, Dinda Maeli; Amalia, Rafa; Siswoyo, Mukarto (International Journal of Social Service and Research, 2025)
This study explores the effectiveness of the Corporate Social Responsibility (CSR) program implemented by RS Pertamina Cirebon in fostering engagement and improving health outcomes within the surrounding community. The CSR initiative primarily targets low-income families, aiming to enhance public health and strengthen the hospital’s relationship with local residents. Employing a descriptive qualitative approach, data were collected through community satisfaction surveys, observations, and in-depth interviews with beneficiaries and hospital stakeholders. Monthly surveys involving up to 1,700 respondents were utilized to evaluate program relevance and effectiveness. The findings indicate that the CSR program has significantly contributed to public health improvement, increased trust between the hospital and the community, and supported the hospital’s brand positioning. Moreover, the study underscores the importance of symmetrical two-way communication in CSR implementation to ensure community needs are met and sustainable outcomes are achieved. Critical success factors include timely execution, transparent cost planning, and the establishment of long-term impact indicators. The research provides practical insights into how healthcare institutions can structure CSR initiatives to deliver both social value and institutional benefits. These findings are relevant not only for RS Pertamina Cirebon but also for other healthcare providers aiming to develop socially responsive and community-centered CSR strategies.